(1386) a developed simplex algorithm for solving transportation problem خوارزمية سيمبلكس مطورة لحل مشكلة النقل - Hamza, Abdel-Kader (The Institute Of National Planning., 2018)
As an economic interpretation of the linear programming model encompassing a wide variety of applications is the following. The modeled system includes several activities which shares limited resources. The objective of the model is to determines the level of each activity that optimizes the output of all activities without violating the limits stipulated on the resources.